2022
DOI: 10.1159/000527262
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects and Mechanisms of Flavonoids in Renal Ischemia-Reperfusion Injury

Abstract: <b><i>Background:</i></b> Acute kidney injury (AKI) is a common and potentially fatal complication encountered during a variety of kidney surgeries. Renal ischemia/reperfusion (I/R) injury is the predominant mechanism of AKI in this setting. Hence, controlling I/R injury is a key research imperative as it is directly related to the prognosis of patients. <b><i>Summary:</i></b> In the last decade, studies in vitro and in animal models have demonstrated that flavon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 78 publications
1
8
0
Order By: Relevance
“…Administering RAL prior to ischemia induction resulted in a reduction in serum levels of urea and creatinine. This outcome is consistent with findings from other studies [34], which can be attributed to the anti-inflammatory impact of RAL, manifested by a significant downregulation of TNF-α and other cytokines in renal parenchymal cells [35].…”
Section: Discussionsupporting
confidence: 92%
“…Administering RAL prior to ischemia induction resulted in a reduction in serum levels of urea and creatinine. This outcome is consistent with findings from other studies [34], which can be attributed to the anti-inflammatory impact of RAL, manifested by a significant downregulation of TNF-α and other cytokines in renal parenchymal cells [35].…”
Section: Discussionsupporting
confidence: 92%
“…The role of oxidative stress in the induction of organ damage following ischemia‒reperfusion has been thoroughly described in the literature [ 25 ]. However, the full molecular mechanisms underlying oxidative stress damage still need to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, researchers reported that intraperitoneal administration of fisetin (20 mg/kg) 15 minutes before surgery attenuated I/R-induced mitochondrial dysfunction, restored mitochondrial copy number, modulated Pgc1 gene expression, reduced mitochondrial fission, enhanced mitochondrial fusion, and promoted mitochondrial autophagy. These actions collectively counteracted the I/R-related reduction in mitochondrial mass in renal tissue (72).…”
Section: Anothermentioning
confidence: 92%